2009
DOI: 10.1007/s11669-009-9579-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Assessment of the Si-Ta and Si-W Systems

Abstract: The knowledge of phase diagram and thermodynamic properties of the Si-Ta and Si-W systems is of technical importance for metallic contacts between Ta, W, and SiC in electrical and electronic devices. The phase diagram and thermodynamic properties of the Si-Ta and Si-W systems were assessed using the CALPHAD approach with available experimental data. The intermetallic compounds of the two systems were modeled as stoichiometric ones. A set of self-consistent thermodynamic parameters were obtained and the calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…For the experiment at temperatures from 0 to 300°C at 30 MPa, round cross-sectional flexible fused silica capillary tube was used. The sample preparation procedures were similar to those described in our previous studies, [36,40] including the following steps: (1) load an aqueous solution column (15 mm long) into a large capillary tube (665 μm OD and 300 μm ID for pressure less than or equal to 50 MPa) with one end closed; (2) insert a small tube (200 μm OD and 75 μm ID) to a certain length (10 mm) away from the end of the large tube to inject a mercury column (approximately 5 mm in length) into the aqueous solution; (3) the capillary high-pressure optical cell containing a NaCl solution at a specific concentration was connected to a high pressure line ( Fig. 1b) and fixed at the experiment table to ensure that the capillary optical cell does not move during measurements at different temperatures.…”
Section: Apparatus and Sample Preparation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For the experiment at temperatures from 0 to 300°C at 30 MPa, round cross-sectional flexible fused silica capillary tube was used. The sample preparation procedures were similar to those described in our previous studies, [36,40] including the following steps: (1) load an aqueous solution column (15 mm long) into a large capillary tube (665 μm OD and 300 μm ID for pressure less than or equal to 50 MPa) with one end closed; (2) insert a small tube (200 μm OD and 75 μm ID) to a certain length (10 mm) away from the end of the large tube to inject a mercury column (approximately 5 mm in length) into the aqueous solution; (3) the capillary high-pressure optical cell containing a NaCl solution at a specific concentration was connected to a high pressure line ( Fig. 1b) and fixed at the experiment table to ensure that the capillary optical cell does not move during measurements at different temperatures.…”
Section: Apparatus and Sample Preparation Proceduresmentioning
confidence: 99%
“…Indeed, the water stretching Raman band is often used as internal standard in the determination of aqueous dissolved species concentration in the molality scale. [24,[31][32][33][34][35][36][37][38][39][40][41][42][43] In our previous works, Ou et al [39,40] found that the Raman peak area ratio (PAR = A CH4 /A H2O ) between the stretching bands of methane and water was affected by temperature and salinity, and the effect of dissolved NaCl on the PAR/mCH 4 (mCH 4 the concentration of CH 4 by mol/kg·H 2 O) became more and more significant with increasing temperature. Nevertheless, the mechanism of the dependence of PAR/mCH 4 on temperature and salinity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the marker plane moves inside the NbSi 2 phase -in a clear contrast to the case of the VSi 2 phase, which indicates comparable diffusion rates of Nb and Si in NbSi 2 . The ratio of In the Ta-Si system, as can be seen in Figure 3(a), four phases are present [69]. However, only two phases, TaSi 2 and Ta 5 Si 3 could be detected in the interdiffusion zone, as shown in Figure 3(b) [46].…”
Section: Philosophical Magazine 1513mentioning
confidence: 90%
“…This indicates that Si has a much higher diffusion rate compared to Si through this phase. The analysis of the diffusion couples gives the value of Figure 5(a) [69]. In the interdiffusion zone, as shown in Figure 5(b), mainly the WSi 2 phase is visible; however, W 5 Si 3 was found as a very thin layer [48].…”
Section: Philosophical Magazine 1513mentioning
confidence: 96%
“…Firstly, we find the isothermal compressibility χ T of the BCC interstitial alloy AB according to Equation (35) and the thermal expansion coefficient α T of the alloy according to Equation (40). The specific capacity at a constant volume of the alloy is given by the following relations [2,29,33]:…”
Section: Introductionmentioning
confidence: 99%